2020
DOI: 10.7717/peerj.9270
|View full text |Cite
|
Sign up to set email alerts
|

Foliar application of abscisic acid mitigates cadmium stress and increases food safety of cadmium-sensitive lettuce (Lactuca sativa L.) genotype

Abstract: Cadmium (Cd2 +) is among the toxic non-essential heavy metals that adversely affect plants metabolic processes and the safety of produce. However, plant hormones can improve plant’s tolerance to various stresses. This study investigated the effect of exogenous abscisic acid (ABA) on the biochemical and physiological processes and food safety of cadmium (Cd2 +)-sensitive lettuce genotype (Lüsu). Seedlings were subjected to five treatme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(11 citation statements)
references
References 57 publications
0
11
0
Order By: Relevance
“…In a study with lettuce (L. sativa), radish (Raphanus sativus), tomato (Solanum lycopersicum) and ryegrass (Secale cereale), it was verified the maximum accumulation of Pb in the roots (Rai et al, 2019), suggesting that immobilization may be linked to the amino acid histidine, consisting of a plant strategy to avoid toxicity in parts above ground (Dawuda et al, 2020). Pb detoxification mechanisms also include storage in the vacuole, synthesis of phytochelatins, and binding to glutathione (Pires-Lira et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…In a study with lettuce (L. sativa), radish (Raphanus sativus), tomato (Solanum lycopersicum) and ryegrass (Secale cereale), it was verified the maximum accumulation of Pb in the roots (Rai et al, 2019), suggesting that immobilization may be linked to the amino acid histidine, consisting of a plant strategy to avoid toxicity in parts above ground (Dawuda et al, 2020). Pb detoxification mechanisms also include storage in the vacuole, synthesis of phytochelatins, and binding to glutathione (Pires-Lira et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…The Cd was found to impair the nutrient balance and accumulation ( Matraszek et al, 2016 ; Wu et al, 2017 ). In oilseed rape and lettuce, Cd stress caused an imbalance of mineral elements ( Xu et al, 2016 ; Dawuda et al, 2020 ). It was found that AMF could increase the nutrient absorption of Guar ( El-Sawah et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…The self-sufficiency rate of food in a place is between 90 and 95%, indicating that the food security of the place is basically safe. The self-sufficiency rate of grain in a place is higher than 95%, indicating that the place can already rely on local grain to achieve self-satisfaction ( Dawuda et al, 2020 ). Meanwhile, the main factors affecting grain production are concentrated in the following aspects.…”
Section: Methodsmentioning
confidence: 99%